PRACTICE OF DOKOK TRADITION IN THE PERSPECTIVE OF SHARING ECONOMY - rahoyo, stefanus (Jurnal Dinamika Sosial Budaya, 2021)
The term of sharing economy became very popular, especially after the 2007-2008 economic and financial crisis. While the term sharing economy is problematic in itself, the practice of sharing has actually been practiced by our society for a long time.                             This study aims to examine whether the practice of dokok tradition can be categorized as a sharing economy or not. If the practice of dokok can be categorized as a sharing economy, the logical consequence is that the conception of the sharing economy which has been known must be expanded.With a qualitative approach, this research concludes that dokok tradition is a practice of sharing economy. The research was conducted in Meteseh Village, Semarang City, Central Java, where the local community still practices the dokok tradition to this day.As far as the authors have explored, there has been no research linking the practice of a tradition with the sharing economy. Thus, it will be a theoretical relevance or novelty of this research.The term of sharing economy became very popular, especially after the 2007-2008 economic and financial crisis. While the term sharing economy is problematic in itself, the practice of sharing has actually been practiced by our society for a long time.                             This study aims to examine whether the practice of dokok tradition can be categorized as a sharing economy or not. If the practice of dokok can be categorized as a sharing economy, the logical consequence is that the conception of the sharing economy which has been known must be expanded.With a qualitative approach, this research concludes that dokok tradition is a practice of sharing economy. The research was conducted in Meteseh Village, Semarang City, Central Java, where the local community still practices the dokok tradition to this day.As far as the authors have explored, there has been no research linking the practice of a tradition with the sharing economy. Thus, it will be a theoretical relevance or novelty of this research.